2008
DOI: 10.1158/0008-5472.can-07-6560
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role of Thromboxane Receptors β Isoform in Bladder Cancer Pathogenesis

Abstract: These studies were undertaken to determine the potential role of thromboxane receptors (TP) in bladder cancer. The data reported herein show that expression of the TP-B receptor protein is increased in tissue obtained from patients with bladder cancer and associated with a significantly poorer prognosis (P < 0.005). Bladder cancer cell lines express the TP-B isoform, unlike immortalized nontransformed urothelial cells (SV-HUC) that express only the TP-A isoform. TP-B receptor expression, but not TP-A, promoted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 40 publications
8
68
0
Order By: Relevance
“…to an increase in apoptosis regardless of cell type, which is supported by the previous reports showing that inhibition of TxAS resulted in apoptosis in bladder (Moussa et al, 2008a) and lung (Cathcart et al, 2010) cancer cells, and that treatment with TxA 2 receptor antagonists also caused significant apoptosis in bladder cancer cells (Moussa et al, 2008b).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…to an increase in apoptosis regardless of cell type, which is supported by the previous reports showing that inhibition of TxAS resulted in apoptosis in bladder (Moussa et al, 2008a) and lung (Cathcart et al, 2010) cancer cells, and that treatment with TxA 2 receptor antagonists also caused significant apoptosis in bladder cancer cells (Moussa et al, 2008b).…”
Section: Discussionsupporting
confidence: 82%
“…For example, it has recently been demonstrated that the activation of TxA 2 receptor by I-BOP (another TxA 2 mimetic) promoted cell proliferation in lung A549 (NSCLC) cells (Li and Tai, 2009). In addition, the bladder cancer cells transfected with b-isoform of TxA 2 receptor and stimulated with U46619 resulted in a significant increase in cellular growth rate and PCNA expression (Moussa et al, 2008b). A recent study has also reported that treatment of two NSCLC cell lines with another selective TxAS inhibitor ozagrel induced a significant reduction in cell proliferation (Cathcart et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Here, we showed that NS398, SQ29548, and TP silencing induced apoptosis in two MM cell lines, and U46619 protected MM cells from apoptosis. These findings were consistent with previous data from other cell types (7,49,50). Meanwhile, we found that NS398, SQ29548, and TP silencing elevated caspase 3 activity, and, as expected, U46619 decreased caspase 3 activity, in accordance with flow cytometry results.…”
Section: Discussionsupporting
confidence: 93%
“…As the TXA 2 -TP axis has been implicated in the development of prostate and breast cancer (20,33,47,94,95), the findings herein suggest that aberrant WT1 regulation of TPα expression may contribute to such cancers and potentially to WT itself. In addition, bearing in mind that the TPα and TPβ isoforms display a number of important functional similarities but also differences in terms of their signalling (6) and regulation including in certain cancers (96,97), coupled with the fact that they are regulated by distinct promoters within the TBXA2R gene, it will be of considerable interest to investigate the expression and transcriptional regulation of TPβ in human cancers, in particular in prostate and breast cancer.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%